Transformation of local tourism through sustainable business model for Moncongos water tourism based on innovation and community empowerment - Nurjanah, Dinda Rajma; Sambas, Febriana; Sari, Ira Puspita; Wahyudi, Mochammad Erlangga; Rahmantya, Yanneri Elfa Kiswara (EcoProfit: Sustainable and Environment Business, 2025)
Background: Moncongos Water Tourism, located in Kuningan Regency, West Java, is a premier destination that relies on white-water rafting as its main attraction. However, the fluctuation of river water discharge during the dry season poses a significant challenge in maintaining the sustainability of tourism at this location. This research aims to develop a sustainable business model that addresses dependence on natural conditions by introducing innovative tourism products, empowering local communities, and implementing effective marketing strategies. Method: This study uses a qualitative, descriptive, and exploratory approach to examine the challenges and opportunities in Moncongos water tourism, focusing on the environmental, social, and economic factors affecting its sustainability. Findings: Innovations like flying fox, rappelling, camping, grape cultivation, Mocongos Cafe, and an MSME bazaar engage the local community in roles such as tour guides and small business owners, boosting the economy and fostering ownership. Digital marketing, including social media and influencer strategies, effectively attracts younger tourists seeking authentic experiences. Conclusion: Studi ini menyimpulkan bahwa menggabungkan inovasi produk, pemberdayaan masyarakat, dan pemasaran digital dapat meningkatkan keberlanjutan wisata air Moncongos, yang memberi manfaat bagi ekonomi lokal dan pelestarian lingkungan. Novelty/Originality of this article: This research shows that the combination of product innovation, community empowerment, and digital marketing can enhance the sustainability and attractiveness of Moncongos tourism. This sustainable business model is expected to be applicable to other tourist destinations facing similar challenges. With this approach, Moncongos not only becomes an attractive destination but also supports the local economy and environmental preservation.